Utilization of Village Funds in Improving the Economy of Village Communities - Endang Indartuti (International Journal of Social Science and Business, 2022)
The government has a policy in the form of village funds sourced from the State Revenue and Expenditure Budget (APBN) because not all villages have good sources of income (Yudistira et al., 2019). Without government funds, the implementation of village autonomy will not run well. This study aims to analyze whether the government has invested village money in improving the economy of rural communities. This type of research is a literature study using qualitative descriptive and content analysis techniques. In library and qualitative research, data analysis is sufficient with non-statistical analysis in the form of reduction, display, and verification. The results show the utilization of village funds in 2021, where village funds are distributed in two categories, namely Regular and Independent. The category is determined based on the annual assessment results and determined by the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. The distribution of the 2021 Village Fund in several regions has been delayed. It is due to several administrative problems by the local government and village government. There is an improvement in the 2022 Village Fund allocation policy, which is expected to impact the distribution and utilization process positively. The role of village funds in supporting national economic recovery and handling Covid-19 includes direct cash assistance from village funds, support for Covid-19 handling funds of at least 8% of the allocation of Village Funds, Work-Intensive Village Funds, and stunting management.